Formation of damage periderm in Markies and Challenger potato tubers under the influence of temperature - de Oliveira Salomão Petrucci, Kharen Priscilla; Mota Pereira, Ariana; Contin Ventrella, Marilia; Finger, Fernando Luiz; da Costa Queiroz, Matheus (Revista Ceres, 2023)
The curing before storing the tubers is necessary for the formation of damage periderm, promoting greater post-harvest conservation. In which, the rate curing and the maintenance of the quality of the tubers depends on the temperature. This way, the search aimed to determine the effect of the curing temperature on the regeneration of the damage periderm and on the carbohydrate metabolism of cultivar Markies and Challenger potatoes tubers destined for industry. For this, the curing was carried out for 14 days on tubers with excoriation injury and tubers without excoriation (control) at temperatures of 8, 14 and 20 °C (RH ± 90%). The fresh mass loss rate (FMLR) daily was higher in the excoriation tubers. The excoriation injury and the temperature of 8 °C increased the total soluble sugar (TSS), reducing sugars (RS) and non-reducing sugars (NRS) of the tubers of ‘Markies’ and TSS of ‘Challenger’. The excoriation injury tuber the process of cell division was induced in the periclinal plane, forming phellogen, with few layers of collapsed cortical cells. In both cultivars, at 14 °C the new phellogen became more evident and at 20 °C some layers of a new cork were formed. In ‘Markies’ the development of new periderm was earlier than in ‘Challenger’, even at 8 °C. It is concluded that the temperature of 14 oC provided better curing and regeneration of the excoriation periderm tubers maintain post-fry quality of potatoes destination by industry processing.